The Role of Parents in Instilling the Values of Pancasila in Children Aged 5-6 Years in the Family Environment - Nani, Diah Fitri Ayu Nani; Muntomimah, Siti; Akbar, Mochamad Ramli (International Journal of Business, Law, and Education, 2025)
Parents play an important role in preparing the golden generation to uphold Pancasila values as an integral part of promoting local wisdom. This study used a qualitative approach, a method that produces descriptive data in the form of written and spoken words obtained from the behavior of the people observed. The term descriptive here refers to efforts to collect data aimed at providing accurate interpretations, thereby obtaining a clear picture of the events being studied. Early childhood tends to imitate the behavior of adults around them, especially parents. Therefore, the appropriateness of the values taught greatly affects the effectiveness of the value instillation process. Each principle of Pancasila can be introduced to children through simple but meaningful activities. The discussion revealed that parents play a role in instilling the values of Pancasila in children through the following applications: (1) Inviting children to do activities together, such as inviting them to pray together at the mosque accompanied by both parents. (2) Setting an example for children in applying Pancasila values in daily life, so that children imitate the behavior exemplified by their parents. (3) Accustoming children to practicing Pancasila values in daily life, so that children become accustomed to doing so without coercion from their parents.